Grassroots Charity in China: Case Analysis of a Charity Project Organised by Jane Zhang Fan Club - Kamppuri, Virpi (fi=Turun yliopisto|en=University of Turku|, 2016)
As unregistered grassroots charities do not appear in official statistics in China, they tend to remain unnoticed by scholars. Also as they operate unofficially and avoid publicity, their work is usually not reported by the media. In this research I explore the grassroots charity activity of one pop music fan club from the viewpoint of trust as a sociological concept. I will also establish the general situation on charity in China. By using textual analysis on internet blogs and discussion forums I map the charity project from the discussion of the original idea to the execution and follow up phase. I study the roles the fan club members assume during the project as anonymous participants of internet conversations, as well as concrete active charity volunteers outside of the virtual world. I establish parties, other than the fan club, which are involved in the charity project. Interviews with one of the participant of the project in 2010, 2014 and 2015 bring valuable additional information and help in distributing the questionnaire survey. A quantitative questionnaire survey was distributed among the fan club members to get more detailed information on the motives and attitudes towards official and unofficial charity in China. Because of the inequality in China, the rural minority areas do not have similar educational opportunities as the mostly majority inhabited urban areas, even though the country officially has a nine year compulsory education. Grassroots charities can operate in relative freedom taking some of the government’s burden of social responsibilities if they are not criticizing the authorities. The problem with grassroots charity seems to be lack of sustainability. The lack of trust for authorities and official charities was the reason why the Jane Zhang fan club decided to conduct a charity case unofficially. As a group of people previously unknown to each other, they managed to build mutual trust to carry out the project transparently and successfully, though not sustainably. The internet has provided a new and effective platform for unofficial grassroots charities, who choose not to co-operate with official organisations. On grassroots level charities can have the transparency and trust that lack from official charities. I suggest, that interviewing the real persons behind the internet aliases and finding out what happened outside the discussion forums, would bring a more detailed and outspoken description of the project concerning of the contacts with the local authorities. Also travelling to the site and communicating with the local people in the village would establish how they have experienced the project.